Agritrade: Agricultural and fisheries trade issues for ACP countries: 2010 Compendium - Alpha, Arlene; Goodison, Paul; Gorez, Beatrice; Ponte, Stephano; Stevens, Christopher; Sureau, Solene (Technical Centre for Agricultural and Rural Cooperation, 2010)
The second in a series launched in 2009, this 2010 Compendium offers a collection of critical reviews of issues related to agricultural and fisheries trade for the African, Caribbean and Pacific (ACP) countries published on the Agritrade website between 2009 and 2010.